Prospective Links between Intraindividual Measures of Negative Affect and Physical Well-being among Couples Coping with Cancer - Shelby L. Langer; Michael Todd; Laura S. Porter; Rachel Koffer (Biopsychosocial Science and Medicine, 2026)
Objective: Research examining associations between intraindividual variability in affective experiences and health stems largely from non-clinical samples and individuals versus within a dyadic context. We sought to examine this linkage in couples coping with cancer. Methods: 233 patients with cancer and their spouses/partners (mean age = 52.5) completed twice-daily ecological momentary assessments for 14 days. Nine negative affect items were used to compute intraindividual negative affect means, standard deviations (SDs, capturing overall dispersion), and mean square successive differences (MSSDs, capturing occasion-to-occasion shifts). Upon study entry and 12 months later, participants completed a measure of physical well-being. Within- and across-partner associations between negative affect dynamics and 12-month change in physical well-being were examined using an Actor-Partner Interdependence Model framework. Results: When SD was used as the indicator of negative affect intraindividual variability, higher mean negative affect predicted declines in physical well-being for caregivers (actor effect, P =.035), and greater patient variability predicted declines in caregiver physical well-being (partner effect, P =.036). When MSSD was used as the indicator of intraindividual variability, greater patient variability predicted declines in their own physical well-being more strongly among those with lower average negative affect (patient mean x patient MSSD interaction, P =.021) and for patients whose partners had greater negative affect variability (patient MSSD x caregiver MSSD interaction, P =.013). Conclusions: Future work could examine intervention strategies to minimize negative affect and foster equanimity in this population, potentially tailoring based on participants’ own mean levels and their partner’s variability.